Lean on Pete [videorecording (DVD)] - Vlautin, Willy; Haigh, Andrew, 1973-; Plummer, Charlie, 1999-; Sevigny, Chloë; Zahn, Steve, 1968- (A24 Films, 2018)
Fifteen-year-old Charley Thompson arrives in Portland, Oregon with his single father Ray, both of them eager for a fresh start after a series of hard knocks. While Ray descends into personal turmoil, Charley finds acceptance and camaraderie at a local racetrack where he lands a job caring for an aging Quarter Horse named Lean On Pete. The horse's owner Del Montgomery and his jockey Bonnie help Charley fill the void of his father's absence--until he discovers that Pete is bound for slaughter.